La Transición a juicio en la trilogía negra de Juan Madrid: el hard boiled como vehículo para la crítica y la expresión del desencanto en la España postransicional - Parra Sánchez, Diego Ernesto (Acta Hispanica, 2016)
Unlike countries like United Kingdom, France or The United States, Spain never had a remarkable tradition in the field of Crime Fiction. This lack of solid tradition was the consequence of different causes like censorship, a bad consideration at editorial level and the lack of a deep industrial revolution which brings the urban conflicts which make this type of literature emerge. With the arrival of the democratic Transition, these transformations took place and, as a consequence of this, Spanish Crime Fiction experiments and amazing development born, precisely, with the aim of building up a critical portrait over this political phenomenon and its most relevant milestones taking the hard boiled literary trend from the North American authors as model. Being this one the context reflected by the Juan Madrid´s noir trilogy on Transition, this article intends to display an approach to it and its role as an unbeatable platform to rise up a critical review of this period from three perspectives: the political, the social and economical and that in relation to the media.